Analisis Pemberian Bantuan Sosial Pemerintah Untuk Masyarakat Pra Sejahtera Selama Masa Pandemi Covid 19 di Kota Medan (Studi Kasus : Kecamatan Medan Area) - Febriaty, Hastina; Rahayu, Sri Endang; Hasibuan, Lailan Safina (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
Medan Area sub-district is one of the many sub-districts that was given social assistance by the government during the Covid-19 pandemic. Many people in the area sub-district find it difficult to meet basic needs due to a decrease in income. This decrease in income was caused by many people experiencing a decrease in working hours due to age, as well as layoffs due to the Covid-19 outbreak. This research aims to carry out an analysis of the provision of government social assistance to underprivileged communities during the Covid 19 pandemic in the Medan area sub-district. The research method used is a descriptive qualitative method. The results of this research are that the total number of people in the Medan Area District is 99,993 people, only a small portion of the people receive social assistance with a total of only 4,406 people and is divided into several social assistance categories, namely Basic Food, BST (cash social assistance). ), and PKH (Family Hope Program). From this figure, only 4.4% of the people from the total population recorded in the Medan Area sub-district received social assistance from the government during the current Covid-19 pandemic.